Andanzas españolas de la poesía costarricense - Monge, Carlos Francisco (2006)
Se describe analíticamente un recorrido histórico de los vínculos literarios, culturales y editoriales entre la producción poética costarricense del siglo xx, y la tradición lírica castellana. Sitúa las letras costarricenses en su contexto hispanoamericano, y señala algunos hitos que podrían explicar etapas y aspectos significativos de su desarrollo literario. An analytical description is provided of the literary, cultural and publishing ties existing between Costa Rican twentieth-century poetry and the Spanish lyric tradition. It situates Costa Rican letters in their Latin American context and suggests certain milestones which could explain significant stages and aspects of its literary development.